Genome-wide association study of adipocyte lipolysis in the GENetics of adipocyte lipolysis (GENiAL) cohort - Kulyté, A; Lundbäck, V; Lindgren, CM; Luan, J; Lotta, LA; Langenberg, C; Arner, P; Strawbridge, RJ; Dahlman, I (Elsevier, 2020)
Objectives Lipolysis, hydrolysis of triglycerides to fatty acids in adipocytes, is tightly regulated, poorly understood, and, if perturbed, can lead to metabolic diseases including obesity and type 2 diabetes. The goal of this study was to identify the genetic regulators of lipolysis and elucidate their molecular mechanisms. Methods Adipocytes from abdominal subcutaneous adipose tissue biopsies were isolated and were incubated without (spontaneous lipolysis) or with a catecholamine (stimulated lipolysis) to analyze lipolysis. DNA was extracted and genome-wide genotyping and imputation conducted. After quality control, 939 samples with genetic and lipolysis data were available. Genome-wide association studies of spontaneous and stimulated lipolysis were conducted. Subsequent in vitro gene expression analyses were used to identify candidate genes and explore their regulation of adipose tissue biology. Results One locus on chromosome 19 demonstrated genome-wide significance with spontaneous lipolysis. 60 loci showed suggestive associations with spontaneous or stimulated lipolysis, of which many influenced both traits. In the chromosome 19 locus, only HIF3A was expressed in the adipocytes and displayed genotype-dependent gene expression. HIF3A knockdown in vitro increased lipolysis and the expression of key lipolysis-regulating genes. Conclusions In conclusion, we identified a genetic regulator of spontaneous lipolysis and provided evidence of HIF3A as a novel key regulator of lipolysis in subcutaneous adipocytes as the mechanism through which the locus influences adipose tissue biology.